Metabolite profiling of Althaea officinalis by HPLC-DAD-MS with in silico and in vitro analysis for therapeutic potential - Turumtay, EmineAkyuz; Demir, Adem; Cetiz, Mehmet Veysi; Uludag, Emre Berk; Baltas, Nimet; Yaman, Burak; Turumtay, Halbay (Springer Int Publ Ag, 2023)
Althaea officinalis L. has been widely used traditionally as an herbal tea and for the treatment of cough, mucous membrane irritation, colds, and inflammation. Parts of the plant extracts were analyzed using HPLC-DAD and HPLC-MS/MS. The total phenolic content, radical scavenging activities, and enzyme inhibitions (urease and xanthine oxidase) of the extracts were determined spectroscopically. The main molecules of this plant and their 3D structures were built using the LigPrep module of Schrodinger Maestro 11.5 with the OPLS3 force field. Additionally, these molecules were analyzed for various physical descriptors and pharmaceutically relevant properties for ADME prediction using the QikProp tool of the Schrodinger Suite. Through HPLC- DAD-MS analysis, abundant compounds such as hesperidin, epigallocatechin, myricetin, and apigenin-7glucoside were detected in the extracts. Moreover, the methanol extracts from the flowers showed a higher inhibition effect on xanthine oxidase (XO). In silico results indicated that the thirteen molecules exhibited strong inhibitory activity toward XO. However, according to the ADME results, the overall compounds, except for rutin and hesperidin, displayed low values of violations of Lipinski's rule of five and predicted pharmacokinetic parameters. They also exhibited drug-likeness features with minimal violations. The HPLC-DAD-MS/MS analysis of the extracts from Althaea officinalis revealed a rich phenolic content in this plant. These therapeutic and preventive compounds may be worth considering for isolation and further exploration as natural remedies. [GRAPHICS]
Keywords: Althaea officinalis; Flavonoid; Phenolics; HPLC-DAD-MS; Urease